Leveraging synergies between UAV and Landsat 8 sensors to evaluate the impact of pale lichen biomass on land surface temperature in heath tundra ecosystems - Villoslada, M.; Bergamo, T.; Kolari, T.; Erlandsson, Rasmus; Korpelainen, Pasi; Räsänen, A.; Tahvanainen, Teemu; Tømmervik, H.; Virtanen, T.; Winquist, E.; Kumpula, T. (Elsevier B.V., 2025)
Peer reviewed